2009
DOI: 10.1002/eji.200838922
|View full text |Cite
|
Sign up to set email alerts
|

Early simultaneous production of intranodal CD4 Th2 effectors and recirculating rapidly responding central‐memory‐like CD4 T cells

Abstract: This study characterizes the diversity of CD4 Th cells produced during a Th2 response in vivo. Kinetics of effector and memory cell differentiation by mouse OVA-specific CD4 T cells was followed during primary responses to alum-precipitated OVA. The complexity of the CD4 T response was assessed in nodes draining and distant from the site of immunization for phenotype, location and function. By 3 days IL-4-producing effector CD4 T cells developed in the draining node and a proportion of the responding cells had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 58 publications
2
16
1
Order By: Relevance
“…AFC numbers generated in the response of OTII cell chimeras to alumOVA has previously been shown to peak 7 d after immunization (11). As expected (1,11,31) the response assisted by OTII cells alone predominantly induced switching to IgG1 (Fig. 2B).…”
Section: Cd8 T Cellssupporting
confidence: 71%
See 1 more Smart Citation
“…AFC numbers generated in the response of OTII cell chimeras to alumOVA has previously been shown to peak 7 d after immunization (11). As expected (1,11,31) the response assisted by OTII cells alone predominantly induced switching to IgG1 (Fig. 2B).…”
Section: Cd8 T Cellssupporting
confidence: 71%
“…Although OTI cells produced IFN-γ protein (Fig. 1B, Left), as expected (1,11,31), in those chimeras with OTII cells alone, very few of the OTII cells produced IFN-γ (Fig. 1B, Right).…”
Section: Cd8 T Cellssupporting
confidence: 60%
“…Molecules of a similar size are able to disperse rapidly throughout the host and prime in multiple sites (43), and this explains why T cell activation and proliferation was synchronous after sFliC. In contrast, alum-precipitated proteins given s.c. tend to prime in draining LN, but not necessarily in other sites (44)(45)(46).…”
Section: Discussionmentioning
confidence: 95%
“…This could also be envisioned as a migration phenotype whereby long-lived memory precursors potentially seek sites of low antigen stimulation, or resist re-activation in other ways, such as inhibition of antigen-receptor signaling. Supporting this concept, Serre et al have shown that early Tcm recirculate [248]. …”
Section: The Elusive Source Of Effector Memory T Cellsmentioning
confidence: 99%